Upside-down positioning of a peri-interventional cava filter during endovascular thrombectomy of a septic superior vena cava thrombosis. (August 2022) - Rosenov, Alexander; Haine, Axel; Walti, Laura Naëmi; Capiaghi, Debora; Schindewolf, Marc; Baumgartner, Iris
A 43-year-old male patient with advanced colon carcinoma presented with disseminated staphylococcus aureus bacteremia and central venous catheter associated septic thrombosis of the superior vena cava. Despite appropriate antimicrobial therapy and surgical debridement of distant foci, bacteremia persisted, so an endovascular thrombectomy was performed. Contrary to the usual application, the Capturex® peri-interventional cava filter was positioned upside down, in the direction of the blood flow, in the superior vena cava to prevent septic embolism during mechanical thrombectomy. The wall-adherent septic thrombus was mechanically detached using a RAT fragmentation basket® followed by Aspirex® rotational thrombectomy. Final phlebography showed complete thrombus removal. Small thrombus fragments could be demonstrated in the filter after retrieval. The adapted technique of a reverse positioning of the Capturex® filter in the superior vena cava seems feasible and effective.